Locking plate versus K-wires and cast fixation in lateral closing-wedge osteotomy for cubitus varus deformity - Jianghua Liu; Youzhi He; Qiang Shi; Yongfu Wang (Frontiers Media S.A., 2024)
BackgroundThe aim of this study was to assess the clinical and radiographic outcomes of cubitus varus treatments based on different fixation methods: Locking plate vs. Kirschner-wires (K-wires) and cast fixation.MethodsThis retrospective study of 28 patients was performed in lateral-wedge osteotomy for cubitus varus deformity in our hospital from July 2018 to July 2020. 14 patients in group A were treated by locking plate after lateral closing-wedge osteotomy, whereas other 14 patients were treated by K-wires in group B. We measured the bony union and carrying angle. The clinical and radiographic outcomes were assessed according to the Bellemore criteria.ResultsNo nonunion, neurovascular injury or myositis ossificans was noted at follow-up. In group A, 1 patient with lateral condylar prominence was found. In group B, 2 patients with pinning site infection were treated successfully with oral antibiotics and 2 patients needed revision surgery for residual varus. According to the Bellemore criteria, statistically significant difference was noted between the two groups (P = 0.0458). In the present study, no statistically significant difference was noted in the length of incision and operation time between the 2 groups (P > 0.05). However, the postoperative carrying angle was significantly different at final follow-up between the 2 groups (P < 0.01).ConclusionsCompared with K-wires and cast fixation, we recommend the wedge osteotomy with lateral locking plate to treat the cubitus varus deformity because locking plate could achieve better functional and cosmetic results and stabilize the distal humerus rigidly.